2006
DOI: 10.1021/ja057242p
|View full text |Cite
|
Sign up to set email alerts
|

Pendant Bases as Proton Relays in Iron Hydride and Dihydrogen Complexes

Abstract: The complex trans-[HFe(PNP)(dmpm)(CH(3)CN)]BPh(4), 3, (where PNP is Et(2)PCH(2)N(CH(3))CH(2)PEt(2) and dmpm is Me(2)PCH(2)PMe(2)) can be successively protonated in two steps using increasingly strong acids. Protonation with 1 equiv of p-cyanoanilinium tetrafluoroborate in acetone-d(6) at -80 degrees C results in ligand protonation and the formation of endo (4a) and exo (4b) isomers of trans-[HFe(PNHP)(dmpm)(CH(3)CN)](BPh(4))(2). The endo isomer undergoes rapid intramolecular proton/hydride exchange with an act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 62 publications
2
120
0
Order By: Relevance
“…An understanding of proton transfer precess will be necessary for developing efficient hydrogen production/hydrogen oxidation catalysts. Recently, DuBois and co-workers reported that trans Fe(II) complexes containing the diphosphine ligand with a pendant nitrogen base as the potential model of the iron-iron hydrogenase enzymes can be successively protonated in two steps using increasingly strong acids and a nitrogen atom in a six-membered chelate ring can promote very rapid intra-and intermolecular proton/hydride exchange in octahedral Fe(II) PNP complexes and function as a proton relay for oxidized Fe(III) hydrides as well [24]. Incorporating good donor ligands (cyanide, tertiary phosphines and isonitrile) to the propanedithiolato-bridged dinuclear complex [(l-pdt)Fe 2 (CO) 6 ] (1) that bears remarkable structural similarities with the active site of Fe-Fe hydrogenase renders the iron atoms more electron-rich and more protophilic [17,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of proton transfer precess will be necessary for developing efficient hydrogen production/hydrogen oxidation catalysts. Recently, DuBois and co-workers reported that trans Fe(II) complexes containing the diphosphine ligand with a pendant nitrogen base as the potential model of the iron-iron hydrogenase enzymes can be successively protonated in two steps using increasingly strong acids and a nitrogen atom in a six-membered chelate ring can promote very rapid intra-and intermolecular proton/hydride exchange in octahedral Fe(II) PNP complexes and function as a proton relay for oxidized Fe(III) hydrides as well [24]. Incorporating good donor ligands (cyanide, tertiary phosphines and isonitrile) to the propanedithiolato-bridged dinuclear complex [(l-pdt)Fe 2 (CO) 6 ] (1) that bears remarkable structural similarities with the active site of Fe-Fe hydrogenase renders the iron atoms more electron-rich and more protophilic [17,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have found that ditertiary phosphanes such as those of general formula (R 2 PCH 2 ) 2 N(R) have interesting coordination properties [7,8] including their use in selfassembly reactions through covalent bonds or H-bonding contacts. [2][3][4][5]9] The tetraphenyl-substituted phosphane (Ph 2 PCH 2 ) 2 N(R), closely related to the three-carbon spacer (Ph 2 PCH 2 ) 2 CH 2 [1,3-bis(diphenylphosphanyl)propane, dppp], has been widely utilised in several metal-catalysed reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, bridge cleavage of the dimers {RuCl 2 (η 6 -p-cym)} 2 or {IrCl 2 (η 5 -Cp*)} 2 with 3a gave the κ 1 -P-monodentate complexes RuCl 2 (η 6 -p-cym)(3a) (6) and IrCl 2 (η 5 -Cp*)(3a) (7), respectively, in which the -PAd group is noncoordinating. Reaction of 6 or 7 with AuCl(tht) (tht = tetrahydrothiophene) gave the mixed-metal complexes κ 2 -P,PЈ-µ-RuCl 2 (η 6 -pcym){Ph 2 PCH 2 N(Ph)CH 2 PAd(AuCl)} (8) and κ 2 -P,PЈ-µ-IrCl 2 (η 5 -Cp*){Ph 2 PCH 2 N(Ph)CH 2 PAd(AuCl)} (9). All new compounds have been fully characterised by spectroscopic and analytical methods.…”
Section: Introductionmentioning
confidence: 99%